2012
DOI: 10.1165/rcmb.2011-0203oc
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Response in Asthma

Abstract: Oxygen-sensing prolyl-hydroxylase (PHD)-2 negatively regulates hypoxia-inducible factor (HIF)1-α and suppresses the hypoxic response. Hypoxia signaling is thought to be proinflammatory but also attenuates cellular injury and apoptosis. Although increased hypoxic response has been noted in asthma, its functional relevance is unknown. The objectives of this study were to dissect the mechanisms and role of the hypoxic response in asthma pathophysiology. Experimental studies were conducted in mice using acute and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…In addition, although methacholine (MCH) is often used to verify airway hyperresponsiveness [50,74,90], here, we showed that weekly peri-adolescent MCH treatments effectively induced labored breathing bouts at multiple ages throughout mouse peri-adolescence. Previous studies have demonstrated that late adolescent/early-adult respiratory allergies and inflammation lead to increased anxiety [91].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, although methacholine (MCH) is often used to verify airway hyperresponsiveness [50,74,90], here, we showed that weekly peri-adolescent MCH treatments effectively induced labored breathing bouts at multiple ages throughout mouse peri-adolescence. Previous studies have demonstrated that late adolescent/early-adult respiratory allergies and inflammation lead to increased anxiety [91].…”
Section: Discussionmentioning
confidence: 86%
“…Second, asthma involves unpredictable respiratory distress with heavily labored breathing. This hypoxic state can lead to limited airflow, increased airway muscle activity, risk for respiratory failure, and airway remodeling [49,50]. Given these two distinct symptoms of asthma – lung inflammation and labored breathing – we independently manipulated these two features in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Increased hypoxic responses by the inflamed airway have been observed in asthma and were reported to lead to exacerbations in acute and chronic experimental allergic models of asthma, but not in healthy, noninflamed lung tissue. 29 The increase in oxidative and hypoxic stress responses in asthma coincides with considerable alterations in cellular energy metabolism. Levels of metabolites participating in the tricarboxylic acid cycle were altered in asthma, and fluctuations of metabolites in pathways involved in cellular energy metabolism in the lungs have been observed in mouse models of experimental asthma.…”
Section: Biological Insights Into Asthma Pathophysiology and Treatmentmentioning
confidence: 99%
“…Using a nonspecific HIF1 inhibitor, Huerta-Yepez et al130 have reported that the inhibition of this pathway reduced the allergic inflammation and lung remodeling in an ovalbumin-triggered mouse model. Furthermore, inhibition of PHD2 by ethyl 3,4-dihydroxybenzoic acid, an oxoglutarate analog, has been shown to lead to a dose-dependent increase of airway hyperresponsiveness in a mouse model of asthma, associated with an increased cell infiltration, mucus production, and collagen deposition in the basal membrane of the epithelium 129. Although this data points to a possible protective role of PHD2 in the development of asthma, not much is known regarding the mechanism through which PHD2 seems to mediate these effects.…”
Section: The Role Of Phd2 In Pathologymentioning
confidence: 99%